The Effect of Glucagon-Like Peptide-1 Receptor Agonists and Sodium-Glucose Cotransporter-2 Inhibitors in Patients Prescribed Regular U-500 Insulin. Issue 11 (November 2019) - Meade, Lisa T.; Mannka, Morgan L.
Background: Only 2 small studies have examined the use of glucagon-like peptide-1 (GLP-1) receptor agonists with U-500 insulin, with mixed results. Moreover, there are no studies to our knowledge that have investigated use of sodium-glucose cotransporter-2 (SGLT-2) inhibitors with U-500 insulin therapy.Objective: This research was designed to determine the effectiveness of GLP-1 agonists and SGLT-2 inhibitors in patients already taking U-500 insulin.Methods: A retrospective chart review was conducted on patients using U-500 insulin to which a GLP-1 agonist or SGLT-2 inhibitor was added as their treatment protocol. The primary outcome measure was change in glycosylated hemoglobin (A1C) after 3 to 6 months on the additional therapy. Secondary outcomes included A1C change at 12 months, changes in total daily dose (TDD) of U-500 insulin, body mass index (BMI) and body weight from baseline, and episodes of hypoglycemia.Results: A total of 17 patients were included in the review. The combination of a GLP-1 agonist and/or SGLT-2 inhibitor with U-500 insulin resulted in significant reductions in A1C (0.84%, P = 0.004) and TDD of U-500 insulin (33.5 units, P = 0.031) at the 3- to 6-month interval. Furthermore, statistically significant decreases in mean BMI and body weight were observed 12 months postbaseline. Hypoglycemia occurred in the majority of patients (64.7%).Conclusion and Relevance: This is the first study to examine SGLT-2 inhibitors in combination with U-500 insulin therapy. Clinically, the addition of a GLP-1 agonist and/or SGLT-2 inhibitor can improve A1C and decrease TDD, BMI, and body weight.